Measurement of Fetal Heart Rate Variability on an Electronic Monitor Using a Prototype Electronic Ruler - Hall, Lianna M.; Hannon, Daniel J.; Leisk, Gary G.; Wolfberg, Adam J.; House, Michael D. (American Journal of Perinatology, 2012)
Objective To develop a prototype electronic ruler for assessment of fetal heart rate (FHR) variability on an electronic monitor and test its reliability and accuracy.Study Design A prototype electronic ruler was designed and developed for assessment of FHR variability on electronic monitors. The electronic ruler consisted of horizontal bands that were sized and colored to embed the four FHR variability categories. The reliability and accuracy of using the electronic ruler to assess FHR variability was studied with expert clinicians.Results Intrarater and interrater reliability was moderate for both the electronic ruler and paper strips. The amplitude measurement accuracy of expert variability assessment compared with a gold standard was significantly improved (p < 0.001) with the electronic ruler versus paper strips. The accuracy of subjects’ FHR variability category responses compared with the gold standard revealed no significant difference (p = 0.50) using either display type.Conclusion Performance of the electronic ruler was equivalent to paper strips, which may aid assessment of variability on electronic monitors as paper strips become less prevalent.
Keywords: electronic fetal monitoring; electronic medical records; fetal heart rate interpretation; fetal heart rate variability; human factors engineering